Cover Picture: Luciferase‐free Luciferin Electrochemiluminescence (Angew. Chem. Int. Ed. 46/2022). Issue 46 (27th October 2022) - Belotti, Mattia; El‐Tahawy, Mohsen M. T.; Yu, Li‐Juan; Russell, Isabella C.; Darwish, Nadim; Coote, Michelle L.; Garavelli, Marco; Ciampi, Simone
Abstract : Spectral tuning, from green to red, of luciferin's electrochemiluminescence (ECL) is achieved by electrolyte engineering, demonstrating that this does not require a keto/enol isomerization of the light emitter. Visual mapping of luciferin's ECL enables a straightforward optical measurement of superoxide diffusivity, as described by Michelle L. Coote, Marco Garavelli, Simone Ciampi et al. in their Research Article (e202209670 ).